Characterization of ZnO/MnO2-Doped Li2C03-LiL binary solid electrolyte for lithium ion primary cell / Mohd Khari Omar - Omar, Mohd Khari (Institute of Graduate Studies, UiTM, 2018)
The continuity in all-solid-state lithium ion battery development is very important considering the growing demand for a reliable and safety improved energy storage device. In this work, a solid state electrolyte composed of Li2C03 and Lil was successfully prepared using mechanical milling method followed by low sintering process. The optimized sintering condition of the solid electrolyte was at 60°C for 24 hours. From the measurement, the xLi2C03-yLiI (x = 80, y = 20) solid electrolyte displayed the highest electrical conductivity of 1.03x10-3 Scm-1 at room temperature. The dissociation of Lil has provided supplemental charge carriers for ions transport in the solid, which much higher than that of the pure Li2C03 sample. A noteworthy increase of ionic conductivity up to 1.75x10-3 Scm- 1 was observed at room temperature with the presence of ZnO filler. The enhancement in electrical conductivity could be due to the interaction between ionic species and Lewis acid-base group on the filler surface and hence, improve the dissociation rate of ions in solid. Incorporation of 9 wt.% Mn02 has successfully amplified the overall conductivity of the sample (3.87x10-1 Scm-1) by increasing the available charge carrier concentration and newly established percolation network for the migration of ions. The interactions between ions and filler's surface groups were also responsible for conductivity enhancement in solid by providing coordination sites for ions transport process. FTIR has revealed the complexation between binary electrolytes and oxide fillers. This could be ascribed to the shift of metal-oxygen absorption band in the samples…